Development and field testing a satellite-linked fluorometer for marine vertebrates. Issue 1 (December 2015) - Lander, Michelle; Lindstrom, Todd; Rutishauser, Matthew; Franzheim, Albert; Holland, Melinda
Abstract Background Understanding the responses of marine vertebrates to spatial and temporal variability of primary productivity is fundamental for their conservation and for predicting how they will be affected by climate change. Despite recent advances in biotelemetry, fluorometers have only recently been incorporated into larger transmitting systems. The purpose of this project was to incorporate a miniature fluorometer into a satellite-linked transmitter to provide measures of in situ phytoplankton fluorescence, which were used to calculate chlorophyll-a (chl-a ), a proxy for primary productivity. After evaluating the suitability of commercially available fluorometers, the ECO Puck™ (WET Labs, Philomath, OR), which measures chl-a (0 to 75 µg Chl/L), was first interfaced with an archival instrument (TDR10) manufactured by Wildlife Computers (Redmond, WA, USA) to (1) determine if the interfaced prototype functioned properly, (2) examine data relative to the orientation of the optics, (3) monitor the behavior of tagged animals, and (4) collect a complete dive/sensor record to validate a data reduction routine established for Service Argos and verify performance of the Argos message generation. Results After laboratory and field trials indicated the interfaced archival prototype operated effectively and was robust to animal behavior, housing was constructed to support the ECO Puck™ with the SPLASH10 satellite transmitter, resulting in the AM-A320A-AU Fluorometer (458 g, 11.9 × 5.8 × 6.2 cm). This instrument was deployed on a Steller sea lion (Eumetopias jubatus ) captured at Adak, Alaska, on 9 October 2014. For 3 weeks, 188 messages were transmitted successfully for the first dive exceeding 9.5 m after the top of the hour and included: (1) the chl-a (µg/cl) and temperature (°C) values at 3 m depth, (2) the maximum chl-a value and the temperature and depth values at which it occurred, (3) the chl-a and temperature values at the maximum dive depth (including the depth value), and (4) the sum of all chl-a values from the surface to the maximum depth of the dive. Conclusions Although fluorescence quenching, bio-fouling, and additional calibration of the AM-A320A-AU Fluorometer warrant additional investigation, preliminary data indicated this instrument should be an effective means for providing sub-surface, in situ phytoplankton fluorescence (chl-a ) relative to animal ecology.